2013
DOI: 10.1371/journal.pgen.1003252
|View full text |Cite
|
Sign up to set email alerts
|

Antagonism Versus Cooperativity with TALE Cofactors at the Base of the Functional Diversification of Hox Protein Function

Abstract: Extradenticle (Exd) and Homothorax (Hth) function as positive transcriptional cofactors of Hox proteins, helping them to bind specifically their direct targets. The posterior Hox protein Abdominal-B (Abd-B) does not require Exd/Hth to bind DNA; and, during embryogenesis, Abd-B represses hth and exd transcription. Here we show that this repression is necessary for Abd-B function, as maintained Exd/Hth expression results in transformations similar to those observed in loss-of-function Abd-B mutants. We character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
45
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(54 citation statements)
references
References 56 publications
9
45
0
Order By: Relevance
“…A similar observation is made in the posterior part of the embryo. In the last abdominal segments Exd is cytoplasmic, even though Hth is present there (Rivas et al, 2013). This observation again suggests that the sole presence of Hth is not sufficient to translocate Exd into the nucleus.…”
Section: Discussionmentioning
confidence: 94%
“…A similar observation is made in the posterior part of the embryo. In the last abdominal segments Exd is cytoplasmic, even though Hth is present there (Rivas et al, 2013). This observation again suggests that the sole presence of Hth is not sufficient to translocate Exd into the nucleus.…”
Section: Discussionmentioning
confidence: 94%
“…In these examples, the binding sites mediating this type of regulation do not need to be specific for a single Hox paralog. This regulation often, but not always, depends on the TALE cofactors [14,16], illustrating the diversity of the underlying molecular mechanisms (see also below). Along the same lines, other target genes might be regulated by even more, or in principle all, Hox paralogs and are referred to as paralog non-specific 12,17] (Figure 2).…”
Section: Flavors Of Hox-tale Target Genesmentioning
confidence: 99%
“…Using phenotypic and molecular analyses, it was shown that inappropriate maintenance of Exd/Hth expression in the posterior domain of the Drosophila embryo, where identity is specified by the posterior Hox gene AbdB, phenocopies AbdB loss of function (Rivas et al, 2013). Such an antagonistic relationship also applies to the repression of the limb-suppressing gene Distalless (Dll) by AbdB .…”
Section: Additional Facets Of Hox-pbc Partnershipsmentioning
confidence: 99%